2021
DOI: 10.1097/pcc.0000000000002733
|View full text |Cite
|
Sign up to set email alerts
|

eSIMPLER: A Dynamic, Electronic Health Record–Integrated Checklist for Clinical Decision Support During PICU Daily Rounds

Abstract: OBJECTIVES: Design, implement, and evaluate a rounding checklist with deeply embedded, dynamic electronic health record integration. DESIGN: Before-after quality-improvement study. SETTING:Quaternary PICU in an academic, free-standing children's hospital. PATIENTS:All patients in the PICU during daily morning rounds. INTERVENTIONS:Implementation of an updated dynamic checklist (eSIMPLER) providing clinical decision support prompts with display of relevant data automatically pulled from the electronic health re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Rationales included removing the burden from clinicians in complex situations (eg, monitoring antibiotic use [ 77 ]). Other rationales cited for implementing a CDSS included the following: the CDSS as a separate intervention to address a clinical need or context (eg, reducing the incidence of hospital-acquired infections [ 64 ]), increasing workflow efficacy [ 79 ], improving adherence to clinical guidelines [ 82 ], transforming time-consuming paper versions of a CDSS to a digital version [ 81 , 87 , 104 ], engaging or collaborating with health care workers [ 78 ], and decreasing duplication of tests or health resource waste (eg, duplicates of magnetic resonance imaging scans) [ 84 ]. Other authors noted that their study was a scale-up or modification of an initial pilot of a CDSS [ 80 , 82 , 98 ], that there was existing evidence that validated the use of a CDSS [ 66 ], and contextual factors of the health system (eg, rapid turnover of clinicians) required the implementation of a CDSS [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rationales included removing the burden from clinicians in complex situations (eg, monitoring antibiotic use [ 77 ]). Other rationales cited for implementing a CDSS included the following: the CDSS as a separate intervention to address a clinical need or context (eg, reducing the incidence of hospital-acquired infections [ 64 ]), increasing workflow efficacy [ 79 ], improving adherence to clinical guidelines [ 82 ], transforming time-consuming paper versions of a CDSS to a digital version [ 81 , 87 , 104 ], engaging or collaborating with health care workers [ 78 ], and decreasing duplication of tests or health resource waste (eg, duplicates of magnetic resonance imaging scans) [ 84 ]. Other authors noted that their study was a scale-up or modification of an initial pilot of a CDSS [ 80 , 82 , 98 ], that there was existing evidence that validated the use of a CDSS [ 66 ], and contextual factors of the health system (eg, rapid turnover of clinicians) required the implementation of a CDSS [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Involving staff in technology design (103,104) and implementation planning was recognized as a necessary strategy for improving implementation and sustainability efforts (104), which aligns with many process models in implementation science (105). Although, no studies directly evaluated algorithm implementation into the electronic health record, one study evaluating an integrated rounding checklist in the PICU showed improved outcomes for patients across many of the measured outcomes (106). During implementation planning, the identification of barriers and facilitators is undisputed to facilitate implementation efforts, as highlighted by determinant frameworks (105).…”
Section: Discussionmentioning
confidence: 99%
“…Another article about rounding discussions in this issue examines the impact of unit census and patient acuity on effective discussion (14). Why not enhance your review of the literature on the topic of rounds by looking at similar work in recent issues of PCCM (15–17).…”
Section: What About Rounds and Setting And Implementing Daily Goals O...mentioning
confidence: 99%